Evaluation of the HbA1c Reduction Cut Point for a Nonglycemic Effect on Cardiovascular Benefit of Hypoglycemic Agents in Patients with Type 2 Diabetes Based on Endpoint Events - Yuchao Wu; Lizhi Tang; Fang Zhang; Zhe Yan; Jing Li; Nanwei Tong (International Journal of Endocrinology)
Background. Atherosclerotic cardiovascular disease (ASCVD) is a major cause of death among patients with diabetes but can be improved by certain hypoglycemic agents. However, adjudicating criteria on whether improvements are a glycemic or nonglycemic effect of these agents remain unclear. Methods. Hypoglycemic agents that produce a cardiovascular benefit in nondiabetic patients are considered to do so via a nonglycemic effect. We performed a subgroup analysis for primary and secondary prevention or very high risk of ASCVD in patients with type 2 diabetes (T2DM). Where glycosylated hemoglobin (HbA1c) was reduced to the same extent in a head-to-head comparison, cardiovascular benefits were judged as a nonglycemic effect. Furthermore, by analyzing the endpoints of four important randomized controlled intensive glucose control studies, UKPDS33, ADVANCE, ACCORD, and VADT, we calculated the cut point of HbA1c reduction for a nonglycemic effect on cardiovascular benefit by hypoglycemic agents in ASCVD groups of different severities. Results. For the ASCVD primary prevention group of T2DM, UKPDS33 indicated a reduction in HbA1c < 0.9%, and a cardiovascular benefit within 10 years was considered a nonglycemic effect. For ASCVD secondary prevention or in the very high-risk group, pioglitazone exerted a nonglycemic effect on cardiovascular benefit in nondiabetic patients with insulin resistance; metformin may exert a similar effect in T2DM patients in a head-to-head study. Analysis of T2DM intensive glucose control studies showed a reduction in HbA1c of <1.0%, and a cardiovascular benefit after approximately 5 years was deemed a nonglycemic effect. Conclusions. For ASCVD primary prevention in T2DM, a reduction in HbA1c < 0.9% and a cardiovascular benefit within 10 years were considered a nonglycemic effect. For ASCVD secondary prevention or in a very high-risk population, a reduction in HbA1c < 1.0% and a cardiovascular benefit within about 5 years were also considered a nonglycemic effect.